2019
DOI: 10.1021/acs.jafc.9b02716
|View full text |Cite
|
Sign up to set email alerts
|

Analysis by UPLC–DAD–ESI-MS of Phenolic Compounds and HPLC–DAD-Based Determination of Carotenoids in Noni (Morinda citrifolia L.) Bagasse

Abstract: Noni bagasse is usually wasted after the noni juice extraction process. The purpose of this study was to investigate the phytochemical composition of noni bagasse (with and without seeds) obtained after a 1 week period of a shortterm juice drip-extraction process from over-ripe noni fruit. Totals of free phenolics, flavonoids, condensed tannins, carotenoids, and most of the minerals were higher in bagasse without seeds (NSB) than in bagasse with seeds (WSB), whereas bound phenolics and total and insoluble diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 53 publications
1
12
0
1
Order By: Relevance
“…This compound has been previously reported in M. citrifolia (Barraza‐Elenes et al, 2019) and M. officinalis (Kim et al, 2005). Compound 7 was identified as asperulosidic acid by its exact mass and fragment ions at m/z 269 and 251; it has been previously reported in M. citrifolia (Barraza‐Elenes et al, 2019; Dussossoy et al, 2011). Compound 8 was tentatively described as a saccharide derivative based on bibliographic information (Spínola, Pinto, & Castilho, 2015).…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…This compound has been previously reported in M. citrifolia (Barraza‐Elenes et al, 2019) and M. officinalis (Kim et al, 2005). Compound 7 was identified as asperulosidic acid by its exact mass and fragment ions at m/z 269 and 251; it has been previously reported in M. citrifolia (Barraza‐Elenes et al, 2019; Dussossoy et al, 2011). Compound 8 was tentatively described as a saccharide derivative based on bibliographic information (Spínola, Pinto, & Castilho, 2015).…”
Section: Resultssupporting
confidence: 74%
“…Compound 1 was identified as a disaccharide (two hexosides) based on its exact mass and fragment ions at m / z 179, 161, 143, and 119. Compound 3 was characterized as the iridoid deacetylasperulosidic acid based on its molecular formula and fragment ions at m/z 227, 209, 183, and 165 (Barraza‐Elenes et al, 2019; Heffels, Müller, Schieber, & Weber, 2017). This compound has been previously reported in M. citrifolia (Barraza‐Elenes et al, 2019) and M. officinalis (Kim et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Noni (Morinda citrifolia L.) is a perennial plant belonging to the Rubiaceae family, which stands out for its ability to tolerate environmental stresses, such as salinity (Nivas et al, 2011;Barraza-Elenes et al, 2019). This species can be cultivated in the Brazilian Northeast, a region that has problems with the accumulation of salts in the soil and water sources, especially in semi-arid areas (Lucena et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, noni juice has been used as an herbal drink and is commercially available worldwide. Noni fruit juice is a natural source of numerous bioactive compounds, including phenolic acids, flavonoids, iridoids and coumarin 11 . Previous research revealed that the noni juice does not induce adverse effects in hepatocytes, and renal function or show subchronic oral toxicity 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%